Enhancement of Escherichia coli and Staphylococcus aureus antibiotic susceptibility using sesquiterpenoids - Simões, M. (2008)
The present work examines the potential of sesquiterpenoids to sensitize Escherichia coli and Staphylococcus aureus, and modulate their susceptibility to the standard antibiotics ciprofloxacin, erythromycin, gentamicin and vancomycin. It was tested samples of three sesquiterpenoids: guaiazulene, nerolidol (racemic mixture of the cis and trans isomers) and germacrene D enriched natural extract. Experiments were conducted aiming to assess the antimicrobial effects of the antibiotic-sesquiterpenoid combination on bacterial growth inhibition, by the disc diffusion assay and the minimum inhibitory concentration (MIC) assessment, the bactericidal effects, the post-antibiotic effect (PAE) and the effect on membrane permeability. The data related with the antimicrobial activity evidenced, through the disc diffusion assay, an antibiotic S. aureus antimicrobial activity enhancement by sesquiterpenoids presence. The MIC value for E. coli decreased significantly by sesquiterpenoids combination with ciprofloxacin, erythromycin and gentamicin, and for S. aureus, with all four selected antibiotics. This combination also increased the PAE, with the exception of guaiazulene, which seemed to quench antibiotic antimicrobial action. A moderate correlation between antimicrobial action and impairment of cell membrane function was detected for germacrene D enriched extract, and nerolidol, as single treatments and in combination with antibiotic, while a poor correlation was obtained for guaiazulene. This study provides basis for the evaluation of sesquiterpenoids as alternative or possible synergistic compounds for current antimicrobial chemotherapeutics, showing the practical utility of natural derived products to increase the susceptibility of E. coli and S. aureus.